The Effect of Training and Development on Innovative Behaviour in Organisations - Nardo, Rio; Aprilyani, Ratnasartika (Journal of International Conference Proceedings, 2024)
Innovation is the development of work according to the skills of employees. If the thoughts and actions of employees are creative and innovative, innovation emerges. The need for innovation arises when someone tries to do cognitive work that is not routine. This study aims to test and analyse the effect of Training and Development on employee innovative behaviour. The benefit of this research is to provide information about Training and Development on employee innovative behaviour. The data analysis used in this research is multiple linear regression. The results of this study are simultaneously training and development have a positive and significant effect on employee innovative behaviour. Partially, training has a positive and significant effect on employee innovative behaviour and human resource development has a positive and significant effect on employee innovative behaviour. The author suggests that training activities can be carried out by the company and conduct employee self-development planning so that it can foster innovative behaviour so that the goals of the company can also be carried out.